2020
DOI: 10.3389/fevo.2020.00048
|View full text |Cite
|
Sign up to set email alerts
|

Are We Coexisting With Carnivores in the American West?

Abstract: Human-carnivore coexistence is an oft-stated goal but assumptions about what constitutes coexistence can lead to goal misalignment and undermine policy and program efficacy. Questions about how to define coexistence remain and specific goals and methods for reaching coexistence require refining. Co-adaptation, where humans adapt to carnivores and vice versa, is a novel socioecological framework for operationalizing coexistence but has yet to be comprehensively examined. We explored co-adaptation and two additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 124 publications
(149 reference statements)
0
27
0
Order By: Relevance
“…This emerging pattern of cooccurrence has led to the suggestion that coexistence—persisting wildlife presence in human-dominated landscapes that facilitate life requisites, such as reproduction, via coadaptation between wildlife and people (as in the sense of refs. 14 and 15 )—no longer requires wilderness areas to maintain viable populations of large carnivores ( 16 ). However, views in support of a diminished role of wilderness in the conservation of large carnivores are not universal ( 17 , 18 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This emerging pattern of cooccurrence has led to the suggestion that coexistence—persisting wildlife presence in human-dominated landscapes that facilitate life requisites, such as reproduction, via coadaptation between wildlife and people (as in the sense of refs. 14 and 15 )—no longer requires wilderness areas to maintain viable populations of large carnivores ( 16 ). However, views in support of a diminished role of wilderness in the conservation of large carnivores are not universal ( 17 , 18 ).…”
mentioning
confidence: 99%
“…These data revealed that, despite high rates of bear mortality in human-dominated areas, coexistence is possible via a combination of individual behavioral shifts and connectivity to wilderness areas that rescue bears from extirpation. These mechanisms, paired with shifting social attitudes toward the tolerance of—and coadaptation with—carnivores ( 15 , 31 , 32 ), have facilitated brown bear recolonization, persistence, and increasing densities in many human-dominated landscapes across western North America ( 33 37 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, bears are described in metaphor relative to their human-like traits and behaviors, and can be honored through ceremony or totems, or feared for the risks they can pose (Brunner 2007, Lescureux andLinnell 2010). We determined that to better understand the meanings ascribed to bears, or meanings inherent in the stories people tell about them, a qualitative exploratory approach to reviewing bear stories would be most appropriate (Fraser et al 2006, Gergen 2015, Haddaway et al 2015, Frank et al 2017, Fraser-Celin et al 2018, Lute and Carter 2020. This approach was appropriate given that it provides researchers the flexibility to describe the data rather than constrain data to defined categories (Lute and Carter 2020).…”
Section: Methodsmentioning
confidence: 99%
“…A key to coexistence is mutual adaptations between humans and wildlife, such that both are able to change their behavior, learn from their experiences, and pursue their own interests with respect to each other (Carter & Linnell, 2016;Lute & Carter, 2020). Unlike wildlife, human adaptation strategies are subject to influence by regulation and social norms, and thus capable of being changed through concerted action (Bautista et al, 2019).…”
mentioning
confidence: 99%